Phenomenological Study of Leadership Styles for Gen Z in the Transformation of the World of Work in Sidoarjo - Anggara, Reza Tri; Kusuma, Kumara Adji; Abadiyah, Rifdah (Jurnal Ilmiah Sumber Daya Manusia, 2026)
The transformation of the world of work marked by the entry of Generation Z into the workforce presents new challenges for organizations, especially in determining a leadership style that is in line with the character and expectations of this generation. Generation Z as digital natives tends to prioritize two-way communication, openness, work flexibility, and attention to mental health and psychological well-being. This study aims to analyze the leadership style preferences of Generation Z in the context of changes in the modern world of work. The research used a descriptive qualitative approach with data collection techniques through in-depth interviews with eight Generation Z informants working in various sectors in Sidoarjo Regency, and validated through source triangulation with two Human Resource Management experts. Data analysis was carried out using the thematic analysis method. The results show that Generation Z's leadership style preferences are dynamic and contextual. The democratic leadership style is the main preference because it provides space for participation and respect for opinions, but the laissez-faire style is considered effective in encouraging independence, while the authoritarian style remains relevant in situations that demand decisiveness and speed of decision-making. Based on these findings, this study formulated a new concept in the form of the Generation Z Adaptive-Contextual Leadership Model, which is a leadership model that places a democratic approach as the main foundation with the flexibility of applying directive and delegative styles according to situational demands. This model emphasizes participatory communication, structural flexibility, and responsibility-based assertiveness, so that it is able to answer the needs of Generation Z in modern organizational dynamics.